Lining Up Brains via a Common Representational Space. Issue 8 (August 2016) - Nishimoto, Shinji; Nishida, Satoshi
Abstract : Guntupalli, Haxby, and colleagues have proposed a new quantitative way to align whole-brain functional imaging data. The new technique, searchlight hyperalignment, allows transformations of a subject's brain activity into a latent common representational space and vice versa.